Ultrasound guided erector spinae plane block for postoperative analgesia after augmentation mammoplasty: case series - Altıparmak,Başak (2019)
Abstract Augmentation mammoplasty is the third most frequently performed esthetic surgical procedure worldwide. Breast augmentation with prosthetic implants requires the insertion of an implant under breast tissue, which causes severe pain due to tissue extension and surgical trauma to separated tissues. In this case series, we present the successful pain management of six patients with ultrasound-guided Erector Spinae Plane block after augmentation mammoplasty. In the operating room, all patients received standard monitoring. While the patients were sitting, the anesthesiologist performed bilateral ultrasound-guided erector spinae plane block at the level of T5. Bupivacaine (0.25%, 20 mL) was injected deep to the erector spinae muscle. Then, induction of anesthesia was performed with propofol, fentanyl, and rocuronium bromide. All patients received intravenous dexketoprofen trometamol for analgesia. The mean operation time was 72.5±6 min and none of the patients received additional fentanyl. The mean pain scores of the patients were 1, 2, 2, and 2 at the postoperative 5th, 30th, 60th and 120th minutes, respectively. At the postoperative 24th hour, the mean Numerical Rating Scale score was 1. The mean intravenous tramadol consumption was 70.8±15.3 mg in the first 24 h. None of the patients had any complications related to erector spinae plane block.